Comparing Diode Laser (660 nm) & 8% Arginine Toothpaste vs. Laser Alone for Dentin Hypersensitivity: A Randomized Clinical Trial: Management of dentinal hypersensitivity - Genescia, Simran; Shetty, Neetha J (Journal of Lasers in Medical Sciences, 2025)
Introduction: This study aimed to evaluate the effectiveness of a 660 nm diode laser in combination with 8% arginine-based toothpaste compared to the laser used independently for managing dentinal hypersensitivity (DH). Methods: A total of 12 patients with severe hypersensitivity were included in the study. Selected teeth were randomly assigned to a Test site (diode laser 660 nm+8% arginine toothpaste) and a control site (660 nm diode laser alone). The selected teeth were irradiated using a 660-nm diode laser at 25 mW power for 60 seconds at a 1cm2 area (1.66×10 -6 J/m3 ) in continuous mode using multi-tip low-level laser therapy (LLLT) (8 mm). DH scores were assessed using the VAS and the SCASS at baseline, 15 minutes post-application, and on days 15 and 30. Results: Clinical parameters such as the visual analogue scale (VAS) and Schiff Cold Air Sensitivity Scale (SCASS) were expressed as mean±SD or median with IQR. The 660-nm diode laser with 8% arginine- ontaining toothpaste showed a notable and sustained reduction in mean VAS scores and SCASS scores 15 minutes post-application and on days 15 and 30, compared to the diode laser (660 nm) alone. A P value less than 0.05 was regarded as statistically significant. Conclusion: The adjunctive use of a diode laser (660 nm) with 8% arginine-containing toothpaste shows promise as a treatment alternative for alleviating DH. Unlike conventional desensitizing agents, which predominantly obstruct dentinal tubules or interfere with nerve response, this combination therapy reduces sensitivity immediately and sustainably via two mechanisms: laser-induced nerve modulation and arginine-mediated tubule occlusion. These findings imply that it could serve as a more effective alternative to standard desensitizing toothpaste or laser therapy when used alone.